2021
DOI: 10.3389/fcvm.2021.689101
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Arrest on the Microtubule Highway—A Feature of Heart Failure and Diabetic Cardiomyopathy?

Abstract: A pathophysiological consequence of both type 1 and 2 diabetes is remodelling of the myocardium leading to the loss of left ventricular pump function and ultimately heart failure (HF). Abnormal cardiac bioenergetics associated with mitochondrial dysfunction occurs in the early stages of HF. Key factors influencing mitochondrial function are the shape, size and organisation of mitochondria within cardiomyocytes, with reports identifying small, fragmented mitochondria in the myocardium of diabetic patients. Card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…Thus, the heart muscle is vulnerable to mitochondria damage. Sarah et al first reported the increased mitochondrial fission in the myocardium of diabetic patients [ 45 ]. Lately, other studies found that FA metabolism in the hearts of asymptomatic diabetic patients significantly increased to compensate for the decreased respiratory capacity, suggesting that changes in mitochondrial metabolism are detrimental to the heart [ 46 , 47 ].…”
Section: Heart Changes In Msc Structure Function and Metabolismmentioning
confidence: 99%
“…Thus, the heart muscle is vulnerable to mitochondria damage. Sarah et al first reported the increased mitochondrial fission in the myocardium of diabetic patients [ 45 ]. Lately, other studies found that FA metabolism in the hearts of asymptomatic diabetic patients significantly increased to compensate for the decreased respiratory capacity, suggesting that changes in mitochondrial metabolism are detrimental to the heart [ 46 , 47 ].…”
Section: Heart Changes In Msc Structure Function and Metabolismmentioning
confidence: 99%
“…The emerging role of Miro1 in the development and progression of diseases, particularly neurological disorders, underscores the need for new methods and tools to study this protein in detail at the molecular level (Fatiga et al, 2021;Kassab et al, 2021;Kontou et al, 2021;López-Doménech et al, 2021;Nguyen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The emerging role of Miro1 in the development and progression of diseases, particularly neurological disorders, underscores the need for new methods and tools to study this protein in detail at the molecular level ( Fatiga et al, 2021 ; Kassab et al, 2021 ; Kontou et al, 2021 ; López‐Doménech et al, 2021 ; Nguyen et al, 2021 ). Currently, most studies rely on ectopic expression of genetically modified (tagged) Miro1 ( Kanfer et al, 2015 ; Castro et al, 2018 ; Nemani et al, 2018 ; Fatiga et al, 2021 ) which previously has been shown to affect mitochondrial morphology and transport in living cells ( Fransson et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Miro1 is a tail-anchored mitochondrial outer membrane protein. After combing with the adaptor protein TRAK1/2, Miro1 can recruit motor proteins (such as kinesin) and initiate microtubule-based mitochondrial movement (37). In a cardiomyocytes and cardiac myofibroblasts co-culture system, mitochondrial transport along microtubules in TNTs is mediated by KIF5B, which is a membrane of the kinesin superfamily (23).…”
Section: Mitochondrial Transfer Via Tunneling Nanotubesmentioning
confidence: 99%